Health worker and policy-maker perspectives on use of intramuscular artesunate for pre-referral and definitive treatment of severe malaria at health posts in Ethiopia. (December 2016) - Kefyalew, Takele; Kebede, Zelalem; Getachew, Dawit; Mukanga, David; Awano, Tessema; Tekalegne, Agonafer; Batisso, Esey; Edossa, Wasihun; Mekonnen, Emebet; Tibenderana, James; Baba, Ebenezer; Shumba, Constance; et al.
Abstract Background The World Health Organization (WHO) recommends injectable artesunate given either intravenously or by the intramuscular route for definitive treatment for severe malaria and recommends a single intramuscular dose of intramuscular artesunate or intramuscular artemether or intramuscular quinine, in that order of preference as pre-referral treatment when definitive treatment is not possible. Where intramuscular injections are not available, children under 6 years may be administered a single dose of rectal artesunate. Although the current malaria treatment guidelines in Ethiopia recommend intra-rectal artesunate or alternatively intramuscular artemether or intramuscular quinine as pre-referral treatment for severe malaria at the health posts, there are currently no WHO prequalified suppliers of intra-rectal artesunate and when available, its use is limited to children under 6 years of age leaving a gap for the older age groups. Intramuscular artesunate is not part of the drugs recommended for pre-referral treatment in Ethiopia. This study assessed the perspectives of health workers, and policy-makers on the use of intramuscular artesunate as a pre-referral and definitive treatment for severe malaria at the health post level. Methods In-depth interviews were held with 101 individuals including health workers, malaria focal persons, and Regional Health Bureaus from Oromia and southern nations, nationalities, and peoples' region, as well as participants from the Federal Ministry of Health and development partners. An interview guide was used in the data collection and thematic content analysis was employed for analysis. Results Key findings from this study are: (1) provision of intramuscular artesunate as pre-referral and definitive treatment for severe malaria at health posts could be lifesaving; (2) with adequate training, and provision of facilities including beds, health posts can provide definitive treatment for severe malaria using intramuscular artesunate where referral is delayed or not possible; (3) health workers at health centres and hospitals frequently use the intravenous route because it allows for co-administration of other drugs, but they find the intramuscular route easier to use at the health post level; (4) the reasons commonly cited against the management of severe malaria using intramuscular artesunate at health post level were: lack of capacity to manage complications and fear of irrational drug use; (5) use of intramuscular artesunate at health post level will require evidence on safety and feasibility before policy shift. Conclusion From the perspective of health workers, use of intramuscular artesunate as pre-referral treatment of severe malaria cases at the health post is possible but dependent on training and availability of skilled workers. Use of intramuscular artesunate as definitive treatment at health posts was not supported, however, operational research to establish its feasibility, safety and efficacy was recommended to guide any implementation of such an intervention.